2018
DOI: 10.4103/ijmr.ijmr_1850_16
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping & diagnostic methods for hepatitis C virus

Abstract: Hepatitis C virus (HCV) infection is a blood borne and transfusion-transmitted infection (TTI). It has emerged as one of the major health challenges worldwide. In India, around 12-18 million peoples are infected with HCV, but in terms of prevalence percentage, its looks moderate due to large population. The burden of the HCV infection increases due to lack of foolproof screening of blood and blood products before transfusion. The qualified screening and quantification of HCV play an important role in diagnosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 91 publications
1
28
0
Order By: Relevance
“…HCV infection is characterized by its long time progression to cirrhosis-related HCC [20]. Based on the phylogenetic and sequence analyses of HCV genomes, there are seven genotypes of HCV strains and 67 subtypes upon further classification of each genotype [21]. HCV genotype 4 is considered the most predominant HCV genotype in Egypt [22].…”
Section: (B) Hcv Infectionmentioning
confidence: 99%
“…HCV infection is characterized by its long time progression to cirrhosis-related HCC [20]. Based on the phylogenetic and sequence analyses of HCV genomes, there are seven genotypes of HCV strains and 67 subtypes upon further classification of each genotype [21]. HCV genotype 4 is considered the most predominant HCV genotype in Egypt [22].…”
Section: (B) Hcv Infectionmentioning
confidence: 99%
“…Some of these target only the 5'UTR region, while others target the 5'UTR region as well as core or NS5B regions. Targeting multiple regions is reported to increase the sensitivity of accurate genotype and subgenotype identification (15). In our study, we used commercial sets based on one-step, real-time PCR with primers targeting 5'UTR in the first 14 months and 5'UTR and NS5B in the last 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…Besides viral capsid formation, it also interacts with various cellular proteins and pathways that play an essential role in the HCV life cycle (13). Many studies have demonstrated that the highly conserved HCV core protein plays an important role in the pathogenesis and progression of the disease due to its ability to interact with a wide spectrum of viral and cellular proteins, including protooncogenes.…”
Section: Introductionmentioning
confidence: 99%